 Transitivity.

Let

A ∼ B

and

B ∼ C

for some small f.o.

A

,

B

, and

C

. Then exist a set

X

such

that

X

up

A

and

X

up

B

and

P

X

up

A

=

P

X

up

B

and a set

Y

such that

Y

up

B

and

Y

up

C

and

P

Y

up

B

=

P

Y

up

C

. So

X

Y

up

A

because

P

Y

P

X

up

A

=

P

Y

P

X

up

B

=

P

(

X

Y

)

up

B ⊇ {

X

Y

} ∩

up

B ∋

X

Y .

Similarly we have

X

Y

up

C

. Finally

P

(

X

Y

)

up

A

=

P

Y

P

X

up

A

=

P

Y

P

X

up

B

=

P

X

P

Y

up

B

=

P

X

P

Y

up

C

=

P

(

X

Y

)

up

C

.

Definition 4.

The

rebase

A ÷

A

for a f.o.

A

and a set

A

(base) such that

X

up

A

:

X

A

is

defined by the formula

A ÷

A

=

up

1

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

where “up” is taken for the set of f.o. on

A

.

Proposition 5.

If

X

up

A

:

X

A

then:

1.

A ÷

A

is a f.o.

2.

A ÷

A

∼ A

.

Proof.

1. We need to prove that

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

is a filter on

A

. That it is

an upper set is obvious. It is non-empty because

Y

up

A

:

Y

A

and thus

A

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

. Let

P , Q

∈ {

X

P

A

| ∃

Y

up

A

:

Y

X

}

. Then

P , Q

A

and

P

up

A

:

P

P

and

Q

up

A

:

Q

Q

. So

P

Q

A

and

P

Q

P

Q

. Thus

P

Q

∈ {

X

P

A

| ∃

Y

up

A

:

Y

X

}

.

2.

P

(

A

Base

(

A

))

up

A

=

up

(

A ÷

(

A

Base

(

A

))) =

{

X

P

(

A

Base

(

A

))

| ∃

Y

up

A

:

Y

X

}

=

P

(

A

Base

(

A

))

up

A

=

P

A

up

A

=

{

X

P

A

|

X

up

A}

=

{

X

P

A

| ∃

Y

up

A

:

Y

X , X

Base

(

A

)

}

=

P

(

A

Base

(

A

))

up

(

A ÷

A

)

.

Thus

A ÷

A

∼ A

because

A

Base

(

A

)

X

up

A

for some

X

up

A

and

A

Base

(

A

)

X

Base

(

A

)

∈ {

X

P

A

| ∃

Y

up

A

:

Y

X

}

=

up

(

A ÷

A

)

.

Proposition 6.

A

up

A ⇒

up

(

A ÷

A

) =

P

A

up

A

.

Proof.

Let

A

up

A

. Then up

(

A ÷

A

) =

{

X

P

A

| ∃

Y

up

A

:

Y

X

}

=

{

X

P

A

|

X

up

A}

=

P

A

up

A

.

Lemma 7.

If

A ∼ B

then

Y

up

A

:

Y

X

⇔ ∃

Y

up

B

:

Y

X

for every f.o.

A

,

B

, and a set

X

.

Proof.

We will prove

Y

up

A

:

Y

X

⇒ ∃

Y

up

B

:

Y

X

(the other direction is similar).

We have

P

K

up

A

=

P

K

up

B

for some set

K

such that

K

up

A

,

K

up

B

.

Y

up

A

:

Y

X

⇒ ∃

Y

P

K

up

A

:

Y

X

⇒ ∃

Y

P

K

up

B

:

Y

X

⇒ ∃

Y

up

B

:

Y

X

.

Proposition 8.

If

A ∼ B

then

B

=

A ÷

Base

(

B

)

for every f.o.

A

,

B

.

Proof.

P

Y

up

A

=

P

Y

up

B

for some set

Y

up

A

,

Y

up

B

. There exists a set

X

up

A

such that

X

up

B

. Thus

X

up

A

:

X

Base

(

B

)

and so

A ÷

Base

(

B

)

is a properly defined f.o.

X

up

(

A ÷

Base

(

B

))

X

P

Base

(

B

)

∧ ∃

Y

up

A

:

Y

X

X

P

Base

(

B

)

∧ ∃

Y

up

B

:

Y

X

X

up

B

(the lemma used).

3 Ordering of filters

Below I will define some categories having filter objects (with possibly different bases) as their
objects and some relations having two filter objects (with possibly different bases) as arguments
induced by these categories (defined as existence of a morphism between these two f.o.).

Theorem 9.

card

a

=

card

U

for every ultrafilter

a

on

U

if

U

is infinite.

2

Section 3